Characterisation of human saliva as a platform for oral dissolution medium development - Gittings, Sally; Turnbull, Neil; Henry, Brian; Roberts, Clive J.; Gershkovich, Pavel (Elsevier, 2016)
Human saliva is a biological fluid of great importance in the field of dissolution testing. However, until now, no consensus has been reached on its key characteristics relevant to dissolution testing. As a result, it is difficult to select or develop an in vitro dissolution medium to best represent human saliva. In this study, the pH, buffer capacity, surface tension, viscosity and flow rate of both unstimulated (US) and stimulated (SS) human saliva were investigated in order to provide a platform of reference for future dissolution studies using simulated salivary fluids. Age and gender related differences in a sample size of 30 participants for each parameter were investigated. Significant differences were established between US and SS for all characteristics except surface tension. Therefore, the requirement for using two simulated salivary fluids should be considered when developing an oral dissolution model.